1983
DOI: 10.1037/0012-1649.19.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem: Change and stability between ages 13 and 23.

Abstract: Findings from several studies that have assessed self-esteem at various ages between 13 and 23 are summarized and integrated quantitatively. The data, including some new results from the Monitoring the Future project, show clearly that global self-esteem, as measured by Rosenberg-type scales, increases over that age span. Various methodological pitfalls that could lead to inappropriate conclusions are discussed. We conclude that the burden of proof regarding a rise in reported self-esteem during adolescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(86 citation statements)
references
References 17 publications
9
72
1
4
Order By: Relevance
“…This supports findings of previous studies which have found that males have a tendency to report higher selfesteem [26,33,34,[36][37][38].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This supports findings of previous studies which have found that males have a tendency to report higher selfesteem [26,33,34,[36][37][38].…”
Section: Discussionsupporting
confidence: 82%
“…As to the specific differences according to gender, results show that girls tend to have a poorer self-esteem than boys during adolescence, regardless of the domains taken into consideration [26,[33][34][35][36][37][38][39] studied secondary school adolescents in Malaysia aged between 13 to 17 years old and also found that males obtained higher self-esteem scores than females. In further support, Kling, Hyde, Showers and Buswell's [40] metaanalysis of gender differences in self-esteem supported that males score higher on standard measures of global self-esteem than females, but stressed that the difference is small.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies report a rise in self-esteem during adolescence (Marsh, 1989;McCarthy & Hoge, 1982;Mullis et al, 1992;O'Malley & Bachman, 1983;Prawat, Jones, & Hampton, 1979;Roeser & Eccles, 1998), others report no change (Chubb et al, 1997), and still others report declines (Keltikangas-Jarvinen, 1990;Zimmerman et al, 1997). Some of these inconsistencies may be due to gender differences that are believed to emerge at this age, specifically the tendency for boys to have higher self-esteem than girls (Block & Robins, 1993;Kling, Hyde, Showers, & Buswell, 1999;Major, Barr, Zubek, & Babey, 1999).…”
Section: Adolescencementioning
confidence: 99%
“…For example, some studies show a rise in self-esteem during adolescence (Marsh, 1989;McCarthy & Hoge, 1982;Mullis, Mullis, & Normandin, 1992;O'Malley & Bachman, 1983), whereas others do not (Block & Robins, 1993;Chubb, Fertman, & Ross, 1997;Zimmerman, Copeland, Shope, & Dielman, 1997). Moreover, if self-esteem does drop in adolescence, researchers have yet to determine the age at which the drop begins, when it reaches its lowest level, and when (if ever) it begins to rise.…”
mentioning
confidence: 99%
“…While this view should basically hold true, several qualifications can be made. Self esteem shows an increasing trend from early to late adolescence (O'Malley & Bachman, 1983). Though the successful mastering of steps in one's occupational preparation will contribute to this overal trend, the effects have to be analytically seperated.…”
Section: Occupational Preparationmentioning
confidence: 99%